2017
DOI: 10.18632/oncotarget.17127
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma in hemodialysis patients

Abstract: We investigated the rates and predictors of mortality in hepatocellular carcinoma (HCC) patients who were or were not undergoing long-term hemodialysis. The participants in this retrospective observational study were 1298 HCC patients (60.0 ± 12.1 years old, 72% male), of whom 172 were undergoing hemodialysis and 1126 were not. HCC patients on hemodialysis exhibited a higher hepatitis C virus carrier rate (49.4% versus 39.3%, P = 0.012), lower hepatitis B virus carrier rate (37.2% versus 58.3%, P < 0.001) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Our study showed that high-NLR and low-PNI were independent predictors of OS in early stage HCC patients after RFA. Multivariate analysis also identified other factors, including the serum AFP and ESRD on hemodialysis,which were similar in previous reports 28 , 29 . The finding of high-NLR concurred with the study of Chen et al .…”
Section: Discussionsupporting
confidence: 87%
“…Our study showed that high-NLR and low-PNI were independent predictors of OS in early stage HCC patients after RFA. Multivariate analysis also identified other factors, including the serum AFP and ESRD on hemodialysis,which were similar in previous reports 28 , 29 . The finding of high-NLR concurred with the study of Chen et al .…”
Section: Discussionsupporting
confidence: 87%
“…The rest of the patients died of non-liver related cause such as myocardial infarction and intracranial hemorrhage. Previous studies have demonstrated HCC patients on hemodialysis had a 2.036-fold greater chance of death than HCC patients not on hemodialysis [37] and ESRD has been found to be a predictor of mortality and hemorrhagic complications [38]. The present study identified male gender, age> 65 years, AFP> 20ng/ml, multiple recurrent tumors, and 1 st recurrence occurring within 2 years bear higher risks of 2 nd recurrence after treatment for recurrent HCC.…”
Section: Plos Onesupporting
confidence: 52%
“…The rest of the patients died of non-liver related cause such as myocardial infarction and intracranial hemorrhage. Previous studies have demonstrated HCC patients on hemodialysis had a 2.036-fold greater chance of death than HCC patients not on hemodialysis [ 37 ] and ESRD has been found to be a predictor of mortality and hemorrhagic complications [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution is a severe public health problem in Taiwan. Moreover, Taiwan is an endemic area for liver disease and HCC [10,11]. Therefore, the objective of this study was to examine the long-term effect of ambient PM 2.5 exposure on mortality in this sensitive population.…”
Section: Introductionmentioning
confidence: 99%